Unveiling the Value Proposition: Real Estate Appraisers as Strategic Partners in Business Decision-Making - Al- Zaidan, Ziyad Ibraheem (International Journal of Economic, Finance and Business Statistics, 2023)
This study explores the role of real estate appraisers in strategic decision-making and value enhancement, focusing on planning aspects often overlooked in existing literature. With Saudi Arabia's rapid real estate market growth and increased competition among valuation companies, there is a need for a deeper understanding of the appraisal process and its strategic implications. The study uses a descriptive approach to examine literature reviews, focusing on the establishment of the Saudi Authority for Accredited Valuers (TAQEEM) in 2017. It highlights the strategic significance of real estate appraisers in navigating the complexities of the valuation process and driving value creation for businesses. The study also highlights the multifaceted roles of appraisers in risk management, financial reporting, investment analysis, portfolio management, and market intelligence. It also explores the implications of technological integration in appraisal practices and offers actionable recommendations for maximizing appraiser contributions to business strategy.